Corrosion Inhibition of Aluminum Alloy 5083 - S. Yaro, Aprael; A. Dahyool, Huda (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
The corrosion inhibition of aluminum alloy 5083 by an environment friendly compound called (8- Hydroxyquinoline) in acidic and alkaline solutions of pH (2 and 12) respectively were studied using weight loss and polarization techniques. Also to examine the main and combined effects of the inhibitor concentration, pH, and contact time using factorial experimental design. Results show that corrosion rate decreased with increasing both inhibitor concentration and contact time and increased with increasing pH value. The polarization curves show that 8-hydroxyquinoline is a cathodic inhibitor